“Aspectos que nunca são do conhecimento do público”: o Carnaval de Belo Horizonte pelas lentes da Globo Minas (1974-1983) - Victor Pinheiro Louvisi (2023)
The thesis discusses the Belo Horizonte Carnival through television reports made by the television station Globo Minas, belonging to Grupo Globo. These television reports were captured in the period from 1974 to 1983 and were intended to be used in the station's news programs and are, for the most part, in black and white. They were produced on 16mm film and are on film rolls. This set is part of what was called "Fundo Globo Minas" and is kept in the Museum of Image and Sound of Belo Horizonte – MIS-BH. The research analyzed 25 rolls of films about the Belo Horizonte Carnival of the "Fundo Globo Minas" and the party can be seen in different situations, such as: parade of samba schools and blocks; interviews with representatives of the city government; Tests; Carnival personalities; election of the Momesca court; The general objective of the thesis is to demonstrate the importance of the images of Carnival of the "Fundo Globo Minas" for the memory of the Carnival of Belo Horizonte and analyzes these films as a source of information, as a support of memory and as a journalistic film record in the museum. The specific objectives are to analyze the records of the television news coverage related to the Belo Horizonte Carnival carried out by Globo Minas in the period from 1974 to 1983; discuss the audiovisual collection as a record and source of information; discuss musealization of audiovisual collections; discuss Carnival and the concept of carnivalization; understand how Carnival was experienced in the period covered by the research. The geographic focus of the research is the city of Belo Horizonte. The research carried out in the exploration of this collection is qualitative, descriptive, and documental, and the methodological procedures adopted are based on the dialogic interdisciplinarity between Information Science and the Human and Social Sciences. Therefore, the contribution of authors and the appropriation of concepts constructed in these areas of knowledge are resorted to. The research problem is: in what way, when analyzing the films of the "Fundo Globo Minas" that were produced by Grupo Globo, and seen here as an informational source, memory support and as a musealized journalistic filmic record, can one apprehend and evidence about the Belo Horizonte Carnival in the period from 1974 to 1983? The initial hypothesis was that this constitutive material of the collection-object of investigation of the thesis pointed to be vestiges of what tends to be suppressed, silenced, in a discourse that tends to "hide by showing" (in coverage or television reports of expressions of popular culture. However, when analyzing the films, it was possible to see the Belo Horizonte Carnival of the period and the work of different popular carnival groups in the city, even though it was a material produced by a hegemonic communication company, in this case Grupo Globo. The methodology was developed from the review of the main references, documentary research, observation and selection of films, description, and analysis of the material. The films were also described and analyzed based on the content analysis methodology. Finally, considerations and proposals for the use of the material were made.